Knowledge, Attitude and Practice of Health Care Personnel about Medical Waste Management in Selected Family Health Centers in Mansoura, Egypt - Mohamed, Hanan Hamed; Abd El-Kader, Rabab Gad; Ibrahim, Adel Al-Wehedy (International Journal of Innovative Research in Medical Science, 2019)
Background: Inadequate management of medical waste is a serious problem in many developing countries due to the risks arising to human health and the environment. The study aim was to assess knowledge, attitude and practice of the health care personnel about the medical waste management in the selected family health centers in Mansoura, Egypt. Design: Cross-sectional study approach was utilized. Cluster random sample was used in selecting the family health centers, the health care personnel working in the selected centers were the participant. Knowledge of health care providers was assessed by structured questionnaire. Observation checklists was used to assess their practice and Likert scale questionnaire to assess their attitude. Results: showed incorrect knowledge and improper practices related to different issues handling wastes of chemicals, pressurized containers and radioactive materials in addition, the duration of storage waste among the health care personnel and more than half (57.5%) of them had satisfactory attitude. Conclusion: physician and pharmacists had a good knowledge about waste management while most of them had unsatisfactory practice. Nurses had a satisfactory practice and most of the health care workers had satisfactory attitude towards safe waste management. Recommendations: development of in-service training program in relation to awareness and practices of waste disposal for all health care staff, with continuous monitoring at regular intervals. In addition to written policies or clear guidelines of waste management should be available at the family health centers.